PENGUKURAN DAN PENILAIAN RANAH AFEKTIF DALAM PENDIDIKAN JASMANI - Ngatman Suwito (Jurnal Pendidikan Jasmani Indonesia, 2008)
Physical education programs designed and implemented from preschool to post secondary level are principally for achieving the goals of physical education consist of four aspects. Those aspects are cognitive, psychomotor, affective, and physical domains. The measurement and evaluation of affective domain, like other domains, can be done through physical education teaching programs. The psychological development in the affective domain context such as attitude, behavior, interest, sportsmanship, leadership, social behavior, personality can be measured. Although these psychological features have been seen as side impacts, they become the main purpose in teaching physical education which eventually helps character building. Some instruments that can be used to measure and evaluate affective domain have been constructed to measure those psychological features. They are attitude, behavior, interest, sportsmanship, leadership, social behavior, personality inventory. There are also some established methods and types of scale such as quantitative methods (Likert Scale), semantic differential scale, serial level scale) and qualitative methods (interview and observation). Kata kunci: Pengukuran, Penilaian, Ranah Afektif, Pendidikan Jasmani.